Design and In Vivo Testing of Novel Single-Stage Tendon Graft Using Polyurethane Nanocomposite Polymer for Tendon Reconstruction. Issue 4 (April 2022) - Ajam, Yazan; Midha, Swati; Tan, Arthur C.W.; Blunn, Gordon; Kalaskar, Deepak M.
Abstract: Severe trauma, failure of prior surgical repair, delayed presentation and excessive scarring around the flexor tendon bed often necessitate a two-stage surgical reconstruction, where a silicone spacer is used in the first stage to recreate the fibro-osseous tunnel through which the tendon graft can glide in the second stage. This staged procedure involves great commitment on the part of both patient and surgeon, over the course of several months, involving a prolonged period of rehabilitation that can be quite disruptive to the patient's life and work. Reducing this from a two-stage into a single-stage procedure, therefore, has the potential to reduce rehabilitation time and cost, expedite return to work, and improve outcomes. To address this, we developed polyurethane (PU) nanocomposite, as an engineered tendon sheath, for treatment of delayed flexor tendon division as a single-stage procedure. The clinically conformant tubular grafts were tested for their efficacy in the peroneus tertius tendon of 6 Mule sheep for 3 months. Semi-quantitative histological assessment was carried out by analysing four descriptive layers: tendon, tendon/polymer sheath interface, polymer sheath, and polymer sheath/surrounding tissue. Four (out of 6) of the implanted PU nanocomposites showed moderate to substantial healing of the injured tendons, with minimal adhesion after repair, ensuring good gliding movement. No statistical differences were observed in tendon repair based on intra-regional variation in the explanted grafts, indicating homogeneity in tendon repair. Overall, the PU nanocomposite bears morphological stability and functionality for tendon repair, in single-stage surgical reconstruction, demonstrating promising evidence for clinical translation. Graphical abstract: The longer treatment period and preservation are major obstacles preventing tendon sheath substitutes from reaching clinic. Here, we show that polyurethane nanocomposite (PU), as engineered tubular graft, implanted using single-stage surgical protocol instead of an otherwise two-stage flexor tendon reconstruction, in sheep model lead to substantial tendon repair in 3 months. Image, graphical abstract